PENGOPTIMALAN JARINGAN AIR BERSIH DENGAN MENGGUNAKAN ALGORITMA PRIM DI KECAMATAN MALAKA TIMUR KABUPATEN MALAKA - Maksimus Asa Moruk; Faustianus - Luan; Fried Markus Allung Blegur (Program Studi Matematika, Universitas Timor, 2026)
A network is a group devides that have the same structure and act together to perform certain functions. In this research, researchers studied the microscope of clean water netwoks in East Malaka District, Malaka Regency using the Prim Algortm which aims to determinethe minimum distribution network for an interconnected weighted graph. Apart from that, researchers used volumetrics (measurement of air discharge using a stopwatch) and 5 liter containers/buckets and calculated Hazen Wiliams to calculate how much air discharge from the spring source to teh distination location, namely Felumasin village and Fatumatetek village The type of data used is quantitative data, namely data obtained from research results that are structure or patterned from one study so that it can be read more easily by researchers. The data source used is primary data, namely data obtained directly by researchers at the research location. Based on the results of this analysis, an air flowrate of 3,17 liters/second was obtanied from a spring with a pipe slope of 0,00348258706, a flow velocity of 403,454545 , and energy loss due to a height of 13.951.139,5 . Thus, the overall air discharge calculation results obtaniend from the springs to and using the general Hazen Williams formula are 0,00430088749 liter/second. This shows that the distribution of clean water networks carried out by researchers using the Prim Algorithm is optimal.